An implantable micro-bio-safety battery and a preparation method thereof

CN123018059APending Publication Date: 2026-10-30CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610855849.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-15
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

然而,现有可打印加工的集流体浆料普遍难以匹配锂合金基电池的工作电压窗口,且在有机电解液环境中存在溶解风险,制约了其在可植入电池中的应用

Benefits of technology

本发明制备了一款可植入式、可3D打印的微型柔性生物安全性电池。传统的金属集流体和涂布法制备的电池,不具备柔性、生物安全性、患者植入后不能使用核磁之类的医疗仪器。本发明制备的电池使用可3D打印的无金属集流体浆料,结合一系列安全的电极材料和封装材料,使得电池具有无金属、可柔性、可图案化制备多种形状、生物安全性的特点。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123018059A_ABST
    Figure CN123018059A_ABST
Patent Text Reader

Abstract

The application discloses a micro-nano fabricated implantable micro-biosafety battery and a preparation method thereof. The battery adopts a metal-free carbon nanotube current collector slurry, combines a 3D printing technology to construct a flexible structure, and comprises a lithium-tin alloy negative electrode, a positive electrode sheet and a safety packaging shell. The preparation steps include slurry preparation, electrode printing and layering assembly. The battery overcomes the problems of mechanical mismatch of a rigid structure of a traditional implantable battery and poor biocompatibility of a metal current collector, has good flexibility, biosafety and shape customization, and is suitable for energy supply of an implantable bioelectronic device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the fields of biomedicine and 3D printing technology, specifically relating to an implantable micro-biosafety battery that can be fabricated in micro-nano sizes and its preparation method. Background Technology

[0002] Implantable bioelectronic devices (such as pacemakers) come into direct contact with biological tissues and are widely used in disease treatment and real-time health monitoring. As a key power source for these devices, batteries, in addition to requiring high energy density and stable power output, should also possess safety and flexibility.

[0003] Traditional implantable batteries (such as lithium / carbon fluoride batteries) often use rigid casings (e.g., titanium metal casings). The elastic modulus and deformation behavior of these casings exhibit a significant mechanical mismatch with soft tissue, easily inducing severe foreign body reactions within the body. Furthermore, these batteries typically use copper or aluminum current collectors, which not only make the battery lack overall flexibility but also result in the metal materials themselves lacking biocompatibility, posing safety hazards. Traditional electrode fabrication processes often employ coating methods, requiring the electrodes to be cut into circular or square sheets. This leads to a limited battery configuration, low space utilization after implantation, and difficulty in achieving flexible implantation adaptation.

[0004] Many micro- and nanofabrication technologies, such as 3D printing, have been introduced into the field of flexible battery manufacturing as a precise and convenient method of patterning. However, existing printable current collector slurries are generally difficult to match the operating voltage window of lithium alloy-based batteries and pose a risk of dissolution in organic electrolyte environments, which limits their application in implantable batteries.

[0005] To address the aforementioned issues, this invention provides a current collector slurry that meets the voltage window requirements of lithium alloy-based batteries, is resistant to organic electrolyte corrosion, and is suitable for 3D printing. Furthermore, based on a series of safe materials, a lithium alloy-based battery with implantable flexibility and biocompatibility is constructed. This battery possesses excellent flexibility and designability, enabling diverse shapes and potentially overcoming the technical bottlenecks of existing implantable batteries' rigid structures and limited shapes. Summary of the Invention

[0006] The purpose of this section is to outline some aspects of embodiments of the present invention and to briefly describe some preferred embodiments. Simplifications or omissions may be made in this section, as well as in the abstract and title of this application, to avoid obscuring the purpose of these documents; however, such simplifications or omissions should not be construed as limiting the scope of the invention.

[0007] In view of the problems existing in the above and / or prior art, the present invention is proposed.

[0008] Therefore, the purpose of this invention is to overcome the shortcomings of the prior art and provide an implantable micro-biosafe battery that can be fabricated in micro-nano dimensions.

[0009] To solve the above technical problems, the present invention provides the following technical solution: an implantable micro-biosafety battery that can be fabricated in micro-nano, characterized in that: the implantable micro-biosafety battery includes a metal-free current collector, a lithium-tin alloy negative electrode, a positive electrode, a packaging shell, a separator, and a biocompatible electrolyte; The metal-free current collector is prepared from a current collector slurry that can be micro / nanofabricated, which includes a conductive agent, a binder, and a solvent. The surface of the lithium-tin alloy negative electrode is coated with a polyethylene glycol-paraffin protective layer. The current collector, negative electrode, and positive electrode are all formed in layers on a polyimide substrate using 3D printing. The battery as a whole has a layered flexible structure, consisting of a packaging shell, a negative electrode, a separator, a biocompatible electrolyte, a positive electrode, and a packaging shell.

[0010] As a preferred embodiment of the micro- and nano-fabricable implantable micro-biosafety battery of the present invention, the conductive agent is selected from at least one of carbon nanotubes, graphene, carbon black, and organic polymer conductive agents, the binder is polyvinylidene fluoride, and the solvent is N-methylpyrrolidone.

[0011] As a preferred embodiment of the micro- and nano-fabricable implantable micro-biosafety battery of the present invention, wherein: the current collector slurry is prepared by mixing and stirring carbon nanotube slurry containing dispersant, multi-walled carbon nanotube powder, polyvinylidene fluoride and N-methylpyrrolidone.

[0012] As a preferred embodiment of the micro- and nano-fabricable implantable micro-biosafety battery of the present invention, the negative electrode is formed by printing tin paste onto a current collector to make a tin electrode sheet, which is then assembled with lithium metal into a battery and discharged to 0.01V to form a lithium-tin alloy.

[0013] As a preferred embodiment of the micro- and nano-fabricable implantable micro-biosafety battery of the present invention, wherein the active material of the positive electrode is selected from lithium iron phosphate or carbon fluoride.

[0014] Another objective of this invention is to overcome the shortcomings of the prior art and provide a method for preparing an implantable micro-biosafety battery, characterized by comprising: A 3D-printable current collector slurry is prepared by mixing and stirring carbon nanotube slurry, carbon nanotube powder, polyvinylidene fluoride, and N-methylpyrrolidone. Tin powder, polyvinylidene fluoride, and carbon black were mixed and ground with N-methylpyrrolidone to form a uniform tin paste suitable for 3D printing. A layer of the tin paste was then printed onto a polyimide film using 3D printing. After drying, the tin paste was printed onto the current collector to prepare an electrode with tin loading. This electrode was then assembled with a lithium metal electrode to form a lithium / tin battery. The lithium / tin battery was discharged to 0.01V. After discharge, the lithium / tin battery was transferred to an argon glove box, and the tin electrode was removed and cleaned. This electrode is the lithium-tin alloy negative electrode. A polyethylene glycol-paraffin coating was then applied to the surface of the lithium-tin alloy negative electrode to form a protective layer. The positive electrode active material, binder, and conductive additive are mixed, N-methylpyrrolidone is added, and the mixture is ground to form a uniform slurry suitable for 3D printing, thus obtaining the positive electrode slurry. A layer of current collector slurry is printed on a polyimide film in a layered manner using 3D printing. After drying, the positive electrode slurry is printed on the current collector to obtain the positive electrode sheet. In an argon glove box, lithium bis(oxalateborate) and dipropylene glycol dimethyl ether were mixed and stirred evenly to prepare a biocompatible electrolyte. A flexible battery is fabricated by sequentially placing the encapsulation shell, negative electrode, separator, biocompatible electrolyte, positive electrode, and encapsulation shell in a glove box using a stacked method; first, vacuum pre-sealing is performed to remove gas and excess electrolyte, and then the entire battery is heat-sealed to obtain a flexible battery.

[0015] In a preferred embodiment of the preparation method described in this invention, the mass ratio of the carbon nanotube slurry, carbon nanotube powder, polyvinylidene fluoride, and N-methylpyrrolidone is 5.5:0.2:0.05:0.75. The mass ratio of the tin powder, polyvinylidene fluoride, and carbon black is 7:1.5:1.5. The mass ratio of the positive electrode active material, binder, and conductive additive is 8:1:1.

[0016] As a preferred embodiment of the preparation method described in this invention, the parameters of the 3D printing are as follows: the current collector parameters are air pressure 0.15~0.26MPa, moving speed 8mm / s, and filling gap 0.2~0.25mm; the electrode slurry parameters are air pressure 0.15MPa and moving speed 3.2~9.0 mm / s.

[0017] Another objective of this invention is to overcome the shortcomings of the prior art and provide an application of an implantable micro-biosafety battery, characterized in that: the battery serves as a power supply unit and is applied to implantable bioelectronic devices.

[0018] As a preferred embodiment of the application described in this invention, the implantable bioelectronic device includes a pacemaker and an in vivo health monitoring device.

[0019] Beneficial effects of this invention: This invention presents an implantable, 3D-printable, miniature, flexible, and biosafety-compliant battery. Traditional batteries fabricated using metal current collectors and coating methods lack flexibility, biosafety, and prevent the use of medical instruments like MRI after implantation. The battery prepared in this invention utilizes a 3D-printable, metal-free current collector slurry, combined with a series of safe electrode and encapsulation materials, resulting in a battery that is metal-free, flexible, patternable in various shapes, and biosafety-compliant. Attached Figure Description

[0020] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort. Wherein: Figure 1 This is an optical photograph of the flexible lithium iron phosphate battery prepared in Example 1 of the present invention.

[0021] Figure 2 This is a schematic diagram of the flexible battery of the present invention. The composition and structure of the flexible battery are shown in an exploded view.

[0022] Figure 3 This is a graph showing the viscosity of the 3D-printable current collector slurry of this invention as a function of shear rate.

[0023] Figure 4 The present invention enables the 3D printing of current collector slurry in 50 seconds. -1 The graph shows the viscosity as a function of time at a given shear rate.

[0024] Figure 5 As described in Embodiment 1 of the present invention, electrodes of the desired size and patterns of a special shape are printed using 3D printing current collector slurry.

[0025] Figure 6 This is Example 1 of the present invention, showing the electrochemical data of a lithium-tin alloy formed on a tin electrode during the discharge of a lithium-tin battery.

[0026] Figure 7 This is the charge / discharge performance data of the flexible lithium iron phosphate battery in Example 1 of the present invention.

[0027] Figure 8 This is the discharge performance data of the fluorinated carbon flexible battery in Example 2 of the present invention.

[0028] Figure 9 The flexible battery being fabricated can be implanted into the demonstration diagram.

[0029] Figure 10 Results of the biosafety test (scale bar 200 micrometers) for the electrolyte.

[0030] Figure 11 The results are from the biosafety test (scale bar 200 micrometers) of the electrode material.

[0031] Figure 12 The cycle specific capacity diagram of a coin cell assembled with lithium iron phosphate as the positive electrode, an alloy negative electrode with a polyethylene oxide-paraffin protective coating, and DMM electrolyte, under a cycle condition of 0.2C.

[0032] Figure 13 The results show the cycle performance of the battery prepared in Comparative Example 1. Detailed Implementation

[0033] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the examples in the specification.

[0034] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and those skilled in the art can make similar extensions without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.

[0035] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in different places in this specification does not necessarily refer to the same embodiment, nor is it a single or selective embodiment that is mutually exclusive with other embodiments.

[0036] The raw materials used in this invention are: carbon nanotube slurry (conductive slurry), which is widely available on the market. Its main components are a large amount of N-methylpyrrolidone and a small amount of carbon nanotube powder and its dispersant. In this experiment, the carbon nanotube slurry used was LB116-32 conductive agent from the Duoduo Chemical brand, catalog number NE-000245. The carbon nanotube powder was CNT powder FT6120 from the Duoduo Chemical brand, catalog number NE-000377. All other materials were commercially available.

[0037] Example 1 This embodiment provides a method for preparing a flexible lithium iron phosphate battery, specifically including the following steps: (1) Preparation of 3D printed current collectors: Weigh 5.5g of carbon nanotube slurry containing dispersant, add 0.2g of multi-walled carbon nanotube powder, 0.05g of polyvinylidene fluoride, and 0.75g of N-methylpyrrolidone, mix and stir for 2 hours to prepare a current collector slurry suitable for 3D printing.

[0038] Using a 3D printer, the movement speed of the printing needle (8 mm / s) and the air pressure of the ejected slurry (0.2 MPa) were adjusted to print current collectors of custom shapes and sizes on a polyimide substrate. After drying at 60°C for 6 hours, the current collector for fabricating flexible batteries was obtained.

[0039] (2) Preparation of lithium-tin alloy anode: Metallic tin powder, polyvinylidene fluoride, and carbon black were weighed in a mass ratio of 70:15:15, with a total weight of 1 g. 0.5 mL of N-methylpyrrolidone was added as a dispersant solvent, and the mixture was ground to prepare a uniform slurry suitable for 3D printing.

[0040] Tin paste was 3D printed onto a current collector and dried at 60°C for 6 hours to prepare a tin electrode. The tin-loaded electrode was then assembled with a lithium metal electrode to form a lithium / tin battery, and a lithium-tin alloy anode was prepared by electrochemical deposition.

[0041] In the glove box, tin electrodes, a separator, and a lithium metal sheet are placed sequentially from bottom to top. During placement, 50 μL of commercial electrolyte (1M LiPF6 in EC:EMC (Vol 3:7)) is added to the separator.

[0042] After compression and sealing, the lithium / tin battery is discharged to 0.01V at a current density of 100mA / g. The discharged lithium / tin battery is then transferred to an argon glove box, the tin electrode sheet is removed and cleaned with DMC, and dried to obtain the lithium-tin alloy negative electrode sheet.

[0043] Weigh 25 mg of polyethylene oxide and 100 mg of paraffin wax, add them to 1 mL of toluene, stir at 80 degrees Celsius for 2 hours to obtain a clear solution, then immerse the alloy negative electrode sheet in the clear solution in an argon glove box for 5-10 seconds, remove it, and dry it at 80 degrees Celsius until the surface is dry to obtain a lithium-tin alloy negative electrode sheet with a polyethylene oxide-paraffin (PEO-Wax) coating.

[0044] (3) Preparation of the positive electrode: Lithium iron phosphate, polyvinylidene fluoride, and carbon black were weighed at a mass ratio of 8:1:1, with a total weight of 1 g. 0.2 mL of N-methylpyrrolidone was added as a dispersant solvent, and the mixture was ground to prepare a uniform slurry suitable for 3D printing. The tin slurry was then printed onto a current collector using a 3D printer. After drying at 60°C for 6 hours, a lithium iron phosphate cathode sheet was prepared.

[0045] (4) Preparation of electrolyte: In a glove box where both oxygen and water content are below 0.1 ppm, weigh 38.76 mg of lithium bis(oxalato)borate (LiBOB) and 1 mL of dipropylene glycol dimethyl ether (DMM), mix them thoroughly to form a clear solution, which is the electrolyte.

[0046] (5) Assembly of flexible lithium iron phosphate batteries: Transfer the prepared battery materials to a glove box. Use PP / PE film as the encapsulation material. Stack the encapsulation film, positive electrode, separator, negative electrode, and encapsulation film in sequence.

[0047] First, seal three sides using a heat sealer, then inject 50μL of DMM electrolyte. Perform vacuum pre-sealing to remove excess electrolyte and gas, and finally seal again to obtain a flexible battery.

[0048] Figure 1 This is an optical photograph of the flexible lithium iron phosphate battery prepared in Example 1 of the present invention.

[0049] Figure 2 This is a schematic diagram of the flexible battery of the present invention. The composition and structure of the flexible battery are shown in an exploded view.

[0050] Figure 3 This is a graph showing the viscosity of the 3D-printable current collector slurry of this invention as a function of shear rate. The testing instrument was a rotational rheometer, and the testing temperature was 25 degrees Celsius.

[0051] To print different architectures, the rheological properties and shear-thinning properties of the slurry (its viscosity decreases with increasing shear rate) play a crucial role. These properties allow the slurry's viscoelasticity to be maintained, enabling it to flow smoothly and continuously from the nozzle under mechanical or pneumatic pressure. It can be observed that the slurry viscosity decreases with increasing shear rate.

[0052] Under steady-state conditions, the viscosity of the slurry is close to 10000 Pa·s, which is very high, giving the slurry a certain degree of support when printed on the substrate. At a viscosity as high as 1000 s... -1 At a shear rate of [specific value], the slurry viscosity decreases to approximately 1 Pa·s, allowing the slurry to flow smoothly and continuously from the nozzle under pneumatic pressure. This meets the requirements of a range of direct-writing 3D printing slurries.

[0053] Figure 4 The present invention enables the 3D printing of current collector slurry at 25 degrees Celsius for 50 seconds. -1 The graph shows the viscosity change over time at a given shear rate. It can be observed that at 50 s... -1 At a shear rate maintained for 1500 seconds, the slurry still retained more than 80% of its initial viscosity. This indicates that the slurry has excellent stability and remains stable even under prolonged printing.

[0054] Figure 5 As described in Embodiment 1 of the present invention, electrodes of the desired size and patterns of a special shape are printed using 3D printing current collector slurry.

[0055] Figure 6 This is Example 1 of the present invention, showing the electrochemical data of a lithium-tin battery being discharged, forming a lithium-tin alloy on a tin electrode. The discharge current is 0.2 mA. It can be seen that after assembling the tin electrode sheet prepared by 3D printing with lithium metal into a battery, the battery discharges normally, and lithium is successfully deposited on the tin electrode, forming a lithium-tin alloy negative electrode.

[0056] Figure 7 The data provided pertains to the charge / discharge performance of the flexible lithium iron phosphate battery in Example 1 of this invention. The charge / discharge current is 0.1 mA, and the operating voltage range is 2.8~3.8V. The battery can be charged and discharged normally, maintaining a charge / discharge efficiency of approximately 100% after 10 cycles.

[0057] Example 2 This embodiment provides a method for preparing a flexible fluorinated carbon battery, specifically including the following steps: (1) Preparation of 3D printed current collectors; Weigh 5.5g of carbon nanotube slurry containing dispersant, add 0.2g of multi-walled carbon nanotube powder, 0.05g of polyvinylidene fluoride, and 0.75g of N-methylpyrrolidone, mix and stir for 2 hours to prepare a current collector slurry suitable for 3D printing.

[0058] Using a 3D printer, the movement speed of the printing needle (8 mm / s) and the air pressure of the ejected slurry (0.2 MPa) were adjusted to print current collectors of custom shapes and sizes on a polyimide substrate. After drying at 60°C for 6 hours, the current collector for fabricating flexible batteries was obtained.

[0059] (2) Preparation of lithium-tin alloy anode: Metallic tin powder, polyvinylidene fluoride, and carbon black were weighed at a mass ratio of 70:15:15, with a total weight of 1 g. 0.5 mL of N-methylpyrrolidone was added as a dispersant solvent, and the mixture was ground to prepare a uniform slurry suitable for 3D printing. The tin slurry was then printed onto a current collector using a 3D printer, and after drying at 60°C for 6 hours, a metallic tin electrode was prepared.

[0060] A lithium / tin battery was assembled by combining a tin-loaded electrode with a lithium metal electrode, and a lithium-tin alloy negative electrode was prepared by electrochemical deposition. In a glove box, the tin electrode, the separator, and the lithium metal sheet were placed sequentially from bottom to top. During placement, 50 μL of commercial electrolyte (1M LiPF6 in EC:EMC (Vol 3:7)) was dropped onto the separator.

[0061] After compression and sealing, the lithium / tin battery is discharged to 0.01V at a current density of 100mA / g. The discharged lithium / tin battery is then transferred to an argon glove box, the tin electrode sheet is removed and cleaned with DMC, and dried to obtain the lithium-tin alloy negative electrode sheet.

[0062] Weigh 25 mg of polyethylene oxide and 100 mg of paraffin wax, add them to 1 mL of toluene, stir at 80 degrees Celsius for 2 hours to obtain a clear solution, then immerse the alloy negative electrode sheet in the clear solution in an argon glove box for 5-10 seconds, remove it, and dry it at 80 degrees Celsius until the surface is dry to obtain a lithium-tin alloy negative electrode sheet with a polyethylene oxide-paraffin (PEO-Wax) coating.

[0063] (3) Preparation of the positive electrode: Fluorocarbon (CF) 0.95 Polyvinylidene fluoride (PVDF) and carbon black were weighed at a mass ratio of 7:1.5:1.5, with a total weight of 1 g. 2.6 mL of N-methylpyrrolidone was added as a dispersant solvent, and the mixture was ground to prepare a uniform 3D-printable slurry. The tin slurry was then printed onto a current collector using a 3D printer. After drying at 60°C for 6 hours, a fluorinated carbon cathode sheet was prepared.

[0064] (4) Preparation of electrolyte: In a glove box where both oxygen and water content are below 0.1 ppm, weigh 38.76 mg of lithium bis(oxalato)borate (LiBOB) and 1 mL of dipropylene glycol dimethyl ether (DMM), mix them thoroughly to form a clear solution, which is the electrolyte.

[0065] (5) Assembly of fluorinated carbon flexible batteries: Transfer the prepared battery materials to a glove box. Use PP / PE film as the encapsulation material. Stack the encapsulation film, positive electrode, separator, negative electrode, and encapsulation film in sequence.

[0066] First, seal three sides using a heat sealer, then inject 50 μL of DMM electrolyte. Perform vacuum pre-sealing to remove excess electrolyte and gas, and finally seal again to obtain a flexible battery.

[0067] Figure 8 The discharge performance data for the fluorinated carbon flexible battery in Example 2 of this invention are as follows: discharge current is 0.1mA, total capacity is 0.7mAh, and the battery is discharging normally.

[0068] Figure 9 This is a demonstration image showing the implantable flexible battery.

[0069] Figure 10 To test the biocompatibility of the electrolyte (scale bar 200 micrometers), mice were subcutaneously injected with 100 μL of the electrolyte and observed for one month. EC+DEC and PC+DME were conventional lithium-ion battery electrolytes, serving as control groups. DMM was the experimental group. It can be seen that the conventional electrolyte caused severe trauma and poor wound healing, indicating high biotoxicity. Mice injected with DMM electrolyte showed no obvious trauma at the injection site. HE sections showed that the EC+DEC and PC+DME groups had extensive inflammatory cell infiltration, while the DMM group showed less inflammatory infiltration. In summary, the DMM electrolyte has good biocompatibility.

[0070] Figure 11 To test the biosafety of the electrode material (scale bar 200 micrometers), electrode pads containing the electrode material were implanted subcutaneously in mice and observed for one month. Compared to the control group without implantation, fluorinated carbon (CF4) showed better biosafety. 0.95 In the lithium iron phosphate (LFP) group and the lithium iron phosphate (LFP) group, no significant pathological changes were observed, indicating good biocompatibility. In the lithium-tin alloy (LiSn) group, severe fibrosis and elevated levels of inflammatory factors were observed at the implantation site in mice. However, when the lithium-tin alloy was coated with a polyethylene glycol-paraffin protective layer (LiSn@PEO-Wax), no significant pathological changes were observed, and the levels of inflammatory factors remained normal, indicating good biocompatibility. This suggests that the lithium-tin alloy requires a polyethylene glycol-paraffin protective layer to reduce the harm caused by the alloy anode after exposure in vivo. Furthermore, [the text abruptly ends here, likely due to an incomplete sentence or missing information]. Figure 12 As can be seen from the cycle specific capacity diagram, the alloy anode coated with a protective coating still maintains excellent electrochemical cycle performance.

[0071] Comparative Example 1 The difference between this comparative example and Example 1 is that the preparation of the electrode in step (2) is replaced by manual coating method. Specifically, the prepared electrode slurry is coated onto the CNT current collector with a scraper and dried. The remaining steps are the same as in Example 1. The electrode and its flexible battery are obtained. The surface uniformity of the obtained electrode is poor and there will be unevenness.

[0072] After being assembled into a pouch cell, under conditions without significant external pressure, poor contact occurs between the battery electrodes and the separator electrolyte, with only a small area in contact, leading to a significant decrease in battery capacity. For example... Figure 13 As shown, the battery capacity decreases with each cycle, exhibiting poorer cycle performance compared to batteries assembled using electrodes made with 3D printed electrodes.

[0073] Comparative Example 2 The difference between this comparative example and Example 1 is that the amount of multi-walled carbon nanotube powder in step (1) is replaced with 0.15g. The remaining steps are the same as in Example 1. The viscosity and conductivity of the current collector slurry are greatly reduced, the printed lines are flat and the shape is difficult to fix, and the electrode resistance increases to 120 ohms.

[0074] Comparative Example 3 The difference between this comparative example and Example 1 is that the amount of multi-walled carbon nanotube powder in step (1) is replaced with 0.25g. The remaining steps are the same as in Example 1. The resulting current collector slurry is relatively viscous and difficult to stir to prepare a uniform slurry. Finally, it cannot be ejected from the needle during printing.

[0075] Comparative Example 4 The difference between this comparative example and Example 1 is that polyvinylidene fluoride is omitted in step (1), while the remaining steps are the same as in Example 1. The printed electrode has poor adhesion and falls off in the electrolyte.

[0076] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the present invention.

Claims

1. A micro / nano-fabrication, implantable, biosafety-enabled battery, characterized in that: The implantable micro biosafety battery includes a metal-free current collector, a lithium-tin alloy negative electrode, a positive electrode, a packaging shell, a separator, and a biocompatible electrolyte. The metal-free current collector is prepared from a current collector slurry that can be micro / nanofabricated, which includes a conductive agent, a binder, and a solvent. The surface of the lithium-tin alloy negative electrode is coated with a polyethylene glycol-paraffin protective layer. The current collector, negative electrode, and positive electrode are all formed in layers on a polyimide substrate using 3D printing. The battery as a whole has a layered flexible structure, consisting of a packaging shell, a negative electrode, a separator, a biocompatible electrolyte, a positive electrode, and a packaging shell.

2. The implantable micro-biosafety battery as described in claim 1, characterized in that: The conductive agent is selected from at least one of carbon nanotubes, graphene, carbon black, and organic polymer conductive agents; the binder is polyvinylidene fluoride, and the solvent is N-methylpyrrolidone.

3. The implantable micro-biosafety battery as described in claim 1, characterized in that: The current collector slurry is prepared by mixing and stirring carbon nanotube slurry containing dispersant, multi-walled carbon nanotube powder, polyvinylidene fluoride and N-methylpyrrolidone.

4. The implantable micro-biosafety battery as described in claim 1, characterized in that: The negative electrode is formed by printing tin paste onto a current collector to create a tin electrode sheet, which is then assembled with lithium metal into a battery and discharged to 0.01V to form a lithium-tin alloy.

5. The implantable micro-biosafety battery as described in claim 1, characterized in that: The active material of the positive electrode is selected from lithium iron phosphate or carbon fluoride.

6. The method for preparing an implantable micro-biosafety battery as described in any one of claims 1 to 5, characterized in that: include, A 3D-printable current collector slurry is prepared by mixing and stirring carbon nanotube slurry, carbon nanotube powder, polyvinylidene fluoride, and N-methylpyrrolidone. Tin powder, polyvinylidene fluoride, and carbon black were mixed and ground with N-methylpyrrolidone to form a uniform tin paste suitable for 3D printing. A layer of the tin paste was then printed onto a polyimide film using 3D printing. After drying, the tin paste was printed onto the current collector to prepare an electrode sheet with tin loading. This electrode sheet was then assembled with a lithium metal electrode sheet to form a lithium / tin battery. The lithium / tin battery was discharged to 0.01V. After discharge, the lithium / tin battery was transferred to an argon glove box, and the tin electrode sheet was removed and cleaned. This electrode sheet is the lithium-tin alloy negative electrode sheet. A polyethylene glycol-paraffin coating was then applied to the surface of the lithium-tin alloy negative electrode sheet to form a protective layer. The positive electrode active material, binder, and conductive additive are mixed, N-methylpyrrolidone is added, and the mixture is ground to form a uniform slurry suitable for 3D printing, thus obtaining the positive electrode slurry. A layer of current collector slurry is printed on a polyimide film in a layered manner using 3D printing. After drying, the positive electrode slurry is printed on the current collector to obtain the positive electrode sheet. In an argon glove box, lithium bis(oxalateborate) and dipropylene glycol dimethyl ether were mixed and stirred evenly to prepare a biocompatible electrolyte. A flexible battery is fabricated by sequentially placing the encapsulation shell, negative electrode, separator, biocompatible electrolyte, positive electrode, and encapsulation shell in a glove box using a stacked method; first, vacuum pre-sealing is performed to remove gas and excess electrolyte, and then the entire battery is heat-sealed to obtain a flexible battery.

7. The preparation method according to claim 6, characterized in that: The mass ratio of the carbon nanotube slurry, carbon nanotube powder, polyvinylidene fluoride, and N-methylpyrrolidone is 5.5:0.2:0.05:0.

75. The mass ratio of the tin powder, polyvinylidene fluoride, and carbon black is 7:1.5:1.

5. The mass ratio of the positive electrode active material, binder, and conductive additive is 8:1:

1.

8. The preparation method according to claim 6, characterized in that: The parameters for the 3D printing are as follows: the current collector parameters are air pressure 0.15~0.26MPa, moving speed 8mm / s, and filling gap 0.2~0.25mm; the electrode slurry parameters are air pressure 0.15MPa and moving speed 3.2~9.0 mm / s.

9. The application of the implantable micro-biosafety battery as described in any one of claims 1 to 5, characterized in that: The battery serves as a power supply unit and is used in implantable bioelectronic devices.

10. The application as described in claim 9, characterized in that: The implantable bioelectronic devices include pacemakers and in vivo health monitoring devices.